Potential drug–drug and drug–disease interactions in well‐functioning community‐dwelling older adults. (22nd January 2017) - Hanlon, J. T.; Perera, S.; Newman, A. B.; Thorpe, J. M.; Donohue, J. M.; Simonsick, E. M.; Shorr, R. I.; Bauer, D. C.; Marcum, Z. A.; ,
Summary: What is known and objective: There are few studies examining both drug–drug and drug–disease interactions in older adults. Therefore, the objective of this study was to describe the prevalence of potential drug–drug and drug–disease interactions and associated factors in community‐dwelling older adults. Methods: This cross‐sectional study included 3055 adults aged 70–79 without mobility limitations at their baseline visit in the Health Aging and Body Composition Study conducted in the communities of Pittsburgh PA and Memphis TN, USA. The outcome factors were potential drug–drug and drug–disease interactions as per the application of explicit criteria drawn from a number of sources to self‐reported prescription and non‐prescription medication use. Results: Over one‐third of participants had at least one type of interaction. Approximately one quarter (25·1%) had evidence of had one or more drug–drug interactions. Nearly 10·7% of the participants had a drug–drug interaction that involved a non‐prescription medication. % The most common drug–drug interaction was non‐steroidal anti‐inflammatory drugs (NSAIDs) affecting antihypertensives. Additionally, 16·0% had a potential drug–disease interaction with 3·7% participants having one involving non‐prescription medications. The most common drug–disease interaction was aspirin/NSAID use in those with history of peptic ulcer disease without gastroprotection. Over one‐third (34·0%) had at least one type of drug interaction. Each prescription medication increased the odds of having at least one type of drug interaction by 35–40% [drug–drug interaction adjusted odds ratio (AOR) = 1·35, 95% confidence interval (CI) = 1·27–1·42; drug–disease interaction AOR = 1·30; CI = 1·21–1·40; and both AOR = 1·45; CI = 1·34–1·57]. A prior hospitalization increased the odds of having at least one type of drug interaction by 49–84% compared with those not hospitalized (drug–drug interaction AOR = 1·49, 95% CI = 1·11–2·01; drug–disease interaction AOR = 1·69, CI = 1·15–2·49; and both AOR = 1·84, CI = 1·20–2·84). What is new and conclusion: Drug interactions are common among community‐dwelling older adults and are associated with the number of medications and hospitalization in the previous year. Longitudinal studies are needed to evaluate the impact of drug interactions on health‐related outcomes.